Assessing the safety and adverse effects of paracetamol, ibuprofen, and their combination in paediatric pain and fever management: A prospective observational study - Vivek Charde; Mukesh Sanklecha; Priyank Rajan; Babar Naeem; Mayur Wanjari; Gaurav Mittal; Tanjmi Djabo Eric Adrien (Journal of Family Medicine and Primary Care)
Purpose: Pain and fever are common paediatric complaints that demand meticulous symptom alleviation to ensure the child’s holistic well-being. Paracetamol, ibuprofen, and their synergistic coadministration occupy a crucial position, rendering the management of these symptoms efficacious. This study aims to evaluate the safety and adverse effects of paracetamol, ibuprofen, and their combination comprehensively. Methods: A prospective observational study was conducted at the Department of Paediatrics, Bombay Hospital Institute of Medical Sciences, Mumbai, India. 108 paediatric patients aged 6 months to 18 years experiencing fever, pain, or both. Patients were assigned to receive one of the three medications and were randomized into one of the three groups: paracetamol, ibuprofen, or a combination. Baseline and 48-hour assessments included vital signs, adverse effects, and biochemical markers including SGOT, SGPT, serum creatinine, platelet count, and occult blood in stool samples. Results: Paracetamol, ibuprofen, and their combination were found to be equally effective in relieving symptoms associated with fever and pain. The most common adverse effect observed was vomiting, with minimal occurrences of rash, cough, and diarrhoea. Biochemical markers, including SGOT, SGPT, serum creatinine, platelet count, and occult blood in stool samples, remained within normal ranges after 48 h of drug administration. Conclusion: This study affirms the safety of paracetamol, ibuprofen, and their combination for paediatric pain and fever management. Minimal adverse effects and the absence of significant biochemical derangements support their favourable risk–benefit profiles, emphasizing their importance in paediatric clinical practice.